GLOBAL ASPECTS OF MICRO- AND MACRO-DEGREE MANAGEMENT INSTALLATION - Iqboljon Odashev Mashrabjonovich, (International Journal of Innovative Technologies in Social Science, 2024)
This paper aims to explore the global aspects of micro- and macro-degree management installation in response to the increasing complexity of modern organizations and the necessity for effective decision-making at different levels. The study investigates various factors, challenges, and strategies related to implementing degree management practices in different organizational contexts. Case studies from diverse industries and global companies are examined to provide a comprehensive understanding of global degree management installation. The findings emphasize the significance of aligning micro and macro aspects of degree management to achieve organizational success in an evolving global environment. By delving into the nuances of degree management installation globally, this manuscript contributes to a deeper understanding of how organizations can effectively manage degrees at both microscopic and macroscopic levels, thereby enhancing decisionmaking and overall organizational performance.